The dynamic simulation of TIS functions in transitions pathways - Jonathan Köhler; Sibylle Braungardt; Tim Hettesheimer; Christian Lerch; Lisa Nabitz; Christian Sartorius; Rainer Walz (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
[Introduction] This paper has the objective of extending the System of Innovation (Kuhlmann and Arnold 2001; figure 1) and Technological Innovation System (TIS) (Bergek et al. 2008) approaches to include pathways of development over time and to include considerations of interactions between niches and the regime from the Multi-Level perspective framework on sustainability transitions (Grin et al. 2010). This should include consideration of consumers and the demand side, which is less comprehensively discussed in the SSI and TIS literature than in the sustainability transitions literature. The reason for this paper is that the SSI has no explanation of dynamics. It is really a typology of actor types which are assumed to be necessary for innovation. TIS is an application of SSI to individual technologies and a more detailed analysis of how successful the innovation system is, using the concept of functions of the innovation systems. These functions then have to be performed successfully for the technology to be taken up. However, there is still no analysis of the interactions between the functions or how interaction determines the evolution of the innovation system through time and its success or failure. Also, a critical aspect of the evolution of technologies and the associated social systems is missing: the feedbacks between the dominant design or regime and the new, alternative technology. The current institutional and market setting is taken as exogenous to the innovation system analysis in the TIS. The analysis is limited to identifying those innovation functions which are being successfully undertaken and those which are weak, together with barriers to the uptake of the new technology and proposing measures to overcome these barriers. Here, the MLP on transitions offers an explicit treatment of niche-regime interactions. [...]
urn:nbn:de:0011-n-4149587
Keywords: 330